5 GHz Band n79 wideband microacoustic filter using thin lithium niobate membrane - Turner, P.J; Garcia, B; Yantchev, V; Dyer, G; Yandrapalli, S; Villanueva, L.G; Hammond, R.B; Plessky, V (Electronics letters, 2019)
Microacoustic resonators made on suspended continuous membranes of LiNbO3 were recently shown to have very strong coupling and low losses at ≥5 GHz, suitable for high-performance filter design. Employing these simple resonator structures, the authors have designed, fabricated, and measured a 4.7 GHz bandpass ladder-type filter having 1 dB mid-band loss and 600 MHz bandwidth to address the 5G Band n79 requirements. The filter is fabricated on a monolithic substrate using standard i-line optical lithography and standard semiconductor processing methods for membrane release, starting with commercially available ion-sliced wafers having 400 nm thickness crystalline LiNbO3 layers. The filter is well-matched to a 50 Ω network and does not require external matching elements. Through accurate resonator engineering using our finite element method software filter design environment, the passband is spurious-free, and the filter provides better-than 30 dB rejection to the adjacent WiFi frequencies. This filter demonstrates the performance and scalable technology required for high-volume manufacturing of microacoustic filters >3.5 GHz.